Benedykt XV, Encyklika "Principi Apostolorum" - Królikowski, Janusz (Vox Patrum, 2024)
With his encyclical "Principi Apostolorum", Pope Benedict XV proclaimed Ephrem the Syrian a Doctor of the universal Church. In this encyclical, Pope Benedict XV justifies this act by referring to the importance of his writings and theology for the Eastern Churches, as well as showing the universal significance of his figure and his theological work. The encyclical has not yet been translated into Polish and therefore deserves to be recalled and to benefit from the inspiration it contains for patristic studies.